Genesis Beginning and Blessing - Hughes, R. Kent (Wheaton Crossway Books, 2004)
"The book of Genesis contains some of the most beautiful and well-known stories in the Bible: the garden, the flood, the tower of Babel, and the lives of the patriarchs. But these are more than just good stories. They lay the groundwork for God's relati
Keywords: Bible. -- Genesis -- Commentaries. Bible. -- Genesis